2017
DOI: 10.1111/nph.14844
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and evolution of MIXTA genes regulating cotton lint fiber development

Abstract: Cotton, with cellulose-enriched mature fibers, is the largest source of natural textiles. Through a map-based cloning strategy, we isolated an industrially important lint fiber development gene (Li ) that encodes an MYB-MIXTA-like transcription factor (MML) on chromosome D12 (GhMML4_D12). Virus-induced gene silencing or decreasing the expression of the GhMML4_D12 gene in n NSM plants resulted in a significant reduction in epidermal cell prominence and lint fiber production. GhMML4_D12 is arranged in tandem wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 52 publications
4
108
0
Order By: Relevance
“…Transcriptome sequencing has repeatedly demonstrated that a high fraction (often 20–40%) of genes in G. hirsutum exhibit A‐ or D‐subgenome biased expression (Yoo & Wendel, ; Liu et al ., ; Zhang et al ., ). In particular, in G. hirsutum the myeloblastosis (MYB)‐MIXTA‐like transcription factor gene GhMML4 ( GhMML4_D12 ), a key regulator of lint (spinnable fiber) development, shows a strong subgenome‐biased expression (Wu et al ., ). We speculate that that selection has shaped gene expression variation through its action on underlying variation in multiple regulatory elements throughout the genome.…”
Section: Discussionmentioning
confidence: 97%
“…Transcriptome sequencing has repeatedly demonstrated that a high fraction (often 20–40%) of genes in G. hirsutum exhibit A‐ or D‐subgenome biased expression (Yoo & Wendel, ; Liu et al ., ; Zhang et al ., ). In particular, in G. hirsutum the myeloblastosis (MYB)‐MIXTA‐like transcription factor gene GhMML4 ( GhMML4_D12 ), a key regulator of lint (spinnable fiber) development, shows a strong subgenome‐biased expression (Wu et al ., ). We speculate that that selection has shaped gene expression variation through its action on underlying variation in multiple regulatory elements throughout the genome.…”
Section: Discussionmentioning
confidence: 97%
“…Long lint fibers (>10 mm) can be easily separated from seeds through the ginning process. Recent studies indicated that both lint and fuzz fibers may share common developmental pathways at least in early differentiation, despite being under different genetic controls (Turley and Kloth, 2002;Wan et al, 2014Wan et al, , 2016Wu et al, 2018;Zhu et al, 2018). Fuzz fibers initiate ?3 to 5 DPA (Stewart, 1975;Wan et al, 2016) and stop elongating ?10 DPA.…”
Section: Unraveling Cotton Fiber Development Using Fiber Mutants In Tmentioning
confidence: 99%
“…A recessive n 2 locus was discovered in 1947 (Ware et al, 1947). Musaev and Abzalov (1972) to be controlled by two loci, n 2 and li 3 , that regulate fuzz and lint fiber initiation, respectively (Zhang and Pan, 1991;Wu et al, 2018). A recent study indicated that the fuzzless phenotype in G. barbadense is mainly due to the presence of the n 2 gene (Zhu et al, 2018).…”
Section: Fiberless Mutantsmentioning
confidence: 99%
See 2 more Smart Citations